Lesbians and lesbianisms : a post-Jungian perspective - Kulkarni, Claudette, 1944- (Routledge, 1997)
Claudette Kulkarni's study of lesbianism explores lesbian experience from both a feminist and Jungian standpoint. Her feminist interpretation challenges the heterosexism embedded in Jungian theory, yet Kulkarni is able to demonstrate that there are links between theory and experience and common ground between Jung and feminism. Using a methodology anchored in Gadamer's hermeneutics, Kulkarni bridges theory and experience by grounding theory in experience rather than by trying to make experience conform to theory.